The island : a novel - Hilderbrand, Elin. (New York : Little, Brown and Co., 2010)
It's the perfect summer getaway-- but some secrets are hard to escape... When her elder daughter abruptly cancels her engagement, and her lavish wedding, Birdie takes both daughters and her cousin to Tuckernuck Island. There dramatic truths are uncovered, old loves are rekindled, and new loves make themselves known.
"A Reagan Arthur Book."
Keywords: Women -- Massachusetts -- Nantucket -- Fiction; Cousins -- Fiction; Female friendship -- Fiction; Vacations -- Fiction; Nantucket Island (Mass.) -- Fiction; Domestic fiction